Pengembangan Media Pembelajaran Matematika Berbasis Android pada Materi Matriks - Epran, Epran; Muhammad, Ilham (LP. Ma'arif Janggan Magetan, 2023)
The use of media in learning can help educators' limitations in conveying information and limited teaching hours in class. One of the ICT-assisted learning media that can be used is learning media that is operated on smartphone devices with the Android operating system. The aim of this research is to determine the validity and practicality of Android-based mathematics learning media on matrix material. The model used follows the ADDIE development model (analysis, design, development, implementation evaluation). The data collection technique used is a non-test technique with data collection instruments, namely validation sheets and practicality sheets. The research results show that Android-based mathematics learning media on matrix material is valid and reliable. The results of the student questionnaire assessment show that this application is not only effective in supporting online and offline learning, but is also able to increase students' interest in learning and deepen their understanding of mathematical concepts. The success of this application creates opportunities to increase learning efficiency, provide relevant learning solutions in the digital era, and motivate students to learn independently.